Comparing Operative Exposures of the Le Fort I Osteotomy and the Expanded Endoscopic Endonasal Approach to the Clivus - Taylor, Christopher I. Sanders; Kurbanov, Almaz; Zimmer, Lee A.; Keller, Jeffrey T.; Theodosopoulos, Philip V. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objectives We compare surgical exposures to the clivus by Le Fort I osteotomy (LFO) and the expanded endoscopic endonasal approach (EEEA).Methods Ten cadaveric specimens were imaged with 1.25-mm computed tomography. After stereotactic navigation, EEEA was performed followed by LFO. Clival measurements included lateral and vertical limits to the midline lower extent of exposure (t test).Results For EEFA and LFO, respectively, maximal lateral exposure in millimeters (mean ± standard deviation) was 24.5 ± 3.7 and 24.5 ±  − 3.8 (p = 0.99) at the opticocarotid recess (OCR) and 25.1 ±  − 4.1 and 24.1 ±  − 3.0 (p = 0.53) at the foramen lacerum level; lateral reach at the hypoglossal canals was 39.0 ±  − 5.88 and 56.1 ±   − 5.3 (p = 0.0004); and vertical extension was 56.0 ±  − 4.1 and 56.3 ±  − 3.4 (p = 0.78).Conclusions For clival exposures, LFO and EEEA were similar craniocaudally and laterally at the levels of the OCR and foramen lacerum. LFO achieved greater exposure at the level of the hypoglossal canal.
Keywords: cadaveric study; clivus; chordoma; expanded endoscopic transsphenoidal approach; Le fort I osteotomy; operative exposure